Black soteriology: the physiological and ontological process - H. M. Mdingi (Acta Theologica)
The Black experience that is historical and continues in post-oppressive and racist regimes proves to be problematic for Black existence. This is particularly so when one considers that the freedom posed by colourlessness and universalism of humanity is an irrational ideal, which works to undermine the level of Black historical oppression, and a denial of justice. This is linked to the untapped reconciliation of the chasm and dichotomy in Black ontological and physiological existence, where their humanity has to be reconciled in both these paradigms for authenticity and even more so for salvation. Such a need ushers in a soteriology that is dialectical in the quest for Black ontology and physiology to allow true affirmation, which is redemption, of Black humanity as Black before God and the world. This soteriology exists through Black theology and the notion of the Black church by encouraging a Black soteriological syllogism.